Analisis penerapan Trust Network Access (ZTNA) dengan penggunaan CAPTCHA pada website umum - Hafizhah Najwa (Technology Sciences Insights Journal, 2024)
The conventional security model centered on network perimeter is no longer adequate given the increasingly complex cyber threats and the rise in digital technology usage. The Zero Trust Network Access (ZTNA) security method emerges as a more effective solution to address these threats. According to ZTNA, no entity can be automatically trusted, whether inside or outside the network, so every access must be validated first. This study examines the concept of ZTNA, its principles, and its implementation stages on a website. The study shows that ZTNA enhances security through strict verification of each user and device via multifactor authentication (MFA) and continuous monitoring of user activity. Although implementing ZTNA presents challenges such as high initial costs and integration complexity, this method offers flexibility, better work mobility, and reduced attack surfaces through contextual access policies and micro-segmentation. This study provides practical guidelines for organizations looking to adopt ZTNA to improve their network security.